Effectiveness of the Notary's Role in Participating in the Implementation of the Provisions of the Money Laundering Crime Law through PMPJ (Principle of Knowing the Service User) - Iftitah, Widya (Activa Yuris: Jurnal Hukum, 2024)
This normative legal research analyzes the effectiveness of the notary's role in preventing money laundering (ML) through the implementation of the Anti-Money Laundering Law through the Know Your Customer (KYC) Principles. The increasing prevalence of ML modus operandi with the potential involvement of notaries serves as the background for this research. The findings indicate that the notary's authority in drafting deeds necessitates the application of the principle of prudence to understand the legal intent and purpose of the client's wishes. ML prevention efforts are also strengthened through technical guidance from the Financial Transaction Reports and Analysis Center (PPATK) to notaries regarding KYC and reporting suspicious financial transactions through the Go-AML application. This research recommends further evaluation of the implementation of KYC by notaries through surveys and analysis to ensure compliance and effectiveness in mitigating ML risks. This research is expected to contribute to the development of policies in notary practices in the prevention and eradication of ML in Indonesia.